Desymmetrization of 7-azabicycloalkenes by tandem olefin metathesis for the preparation of natural product scaffolds - Wolfgang Maison; Marina Büchert; Nina Deppermann (Beilstein Journal of Organic Chemistry, 2007)
Background Tandem olefin metathesis sequences are known to be versatile for the generation of natural product scaffolds and have also been used for ring opening of strained carbo- and heterocycles. In this paper we demonstrate the potential of these reactions for the desymmetrization of 7-azabicycloalkenes. Results We have established efficient protocols for the desymmetrization of different 7-azabicycloalkenes by intra- and intermolecular tandem metathesis sequences with ruthenium based catalysts. Conclusion Desymmetrization of 7-azabicycloalkenes by olefin metathesis is an efficient process for the preparation of common natural product scaffolds such as pyrrolidines, indolizidines and isoindoles.